PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI YAYASAN BADAN WAKAF SULTAN AGUNG DI KOTA SEMARANG - Ahmad Hakim Rifai, 12.52.02.0176; Basiya, Robertus (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to determine the effect of leadership styles and motivation to work on teacher performance organizational culture moderated Foundation Waqaf Board Sultan Agung in Semarang. This study was conducted on teachers within the Foundation Waqaf Board Sultan Agung Semarang with a population of 175 teachers and samples taken 100 teachers. Test instrument used was the validity and reliability of the components of the matrix, while the test model used is the F test and determination, the classical assumption of normality test data and test hiterokedastisitas. Hypothesis test using T test. The purpose of this study to determine: (1) Testing and Analyzing Performance Against Teacher Leadership Style. (2) Testing and Analyzing the Effect of Work Motivation Against Teacher Performance. (3) Test and Analyze How Influence of Organizational Culture on Performance Master. (4) Testing and Analyzing the Effect of moderate Organizational Culture on Performance Leadership Style Guru. (5) Testing and Analyzing the Effect of Organizational Culture moderate Work Motivation Against Teacher Performance. Keywords: Leadership Style, Work Motivation, Organizational Culture, and teacher performance